Five-Year Risk of Basal Cell Carcinoma Recurrence After a Conventional Surgical Excision - Duarte, Bruno (2020)
Introduction: Basal cell carcinomas are mostly treated surgically, mostly by surgery with postoperative histopathologic margin evaluation (“conventional surgery”), but large long-term data regarding recurrence by completeness of excisions is limited. Methods: Retrospective cohort study of basal cell carcinomas treated by conventional surgery at different medical specialties in a large tertiary centre, between 2008 and 2014. Survival analysis with a Cox proportional-hazards was performed, stratified by completeness of excision (complete excision/incomplete excision) and adjusted to several potentially confounding covariates. Results: A total of 2876 basal cell carcinomas were identified, of which 2306 (2100 primary, 206 recurrent) were considered eligible for analysis. During the 5-years of follow-up, there were 80 (4%) recurrences among 1980 complete excisions (16/1000 cases-year) and 83 (23.9%) recurrences among 348 incomplete excisions (100/1000 cases-year). Survival analysis was performed with multivariable adjustment. In the final adjusted model, we identified an association between relapse and re-intervention on recurrent tumors [adjusted Hazard Ratio (HR) 2.20 (95% Confidence interval (IC), 1.26-3.84), p=0.006], a wrong preoperative clinical diagnosis/surgery devoid of preoperative biopsy [adjusted HR 2.75 (95% CI, 1.68-4.5), p<0.001], treatment prior to 2012 [adjusted HR 1.47 (95% IC, 1.06-2.05), p<0.021] and surgery on a high-risk location, accordingly to the NCCN stratification [adjusted HR 2.18 (95% CI, 1.08-4.40), p<0.030]. By specific anatomic location, the likelihood of recurrence was especially high in the nose [adjusted HR 3.18 (95% CI 1.71-5.87), p<0.001] and eyelids [adjusted HR 3.08 (95% CI, 1.32-7.17), p=0.009]. There was also a trend towards higher recurrence in aggressive histological subtypes [adjusted HR 1.43 (95% CI 0.99-2.07), p<0.058]. Conclusion: Recurrent basal cell carcinomas, regardless of location, and primary basal cell carcinomas on high-risk locations of the face, especially on the eyelids and nose, should be considered to have a higher and independent likelihood of recurrence, even on “complete excisions” evaluated by histopathology. On the other hand, wait-andsee approaches in incompletely excised BCCs should be considered against a significant 5-year risk of relapse (1 in 10 lesions).